Principles of European Family Law Regarding the Divorce by the Public Notary in Hungary - Béldi-Turányi, Noémi (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2024)
Thanks to the principles of the Commission on European Family Law on divorce law, extrajudicial divorce by mutual consent is becoming increasingly widespread in many European countries. The possibility of introducing this legal institution was also raised in Hungary in 2012 during the codification of the new Civil Code, but was ultimately rejected. The aim of this study is to examine the possibility of introducing divorce by the public notary as a possible alternative to divorce by mutual consent, in the light of the principles of European Union divorce law as well as the arguments and counter-arguments raised during the codification process.